A Novel Approach to Design a BCD Adder Using Complimentary Logic Gate - Kaushik, Awanish; Choudhary, Shilpa; Bhardwaj, Divya (International Journal of Engineering and Technology, 2018)
A complimentary Logic gate is most broadly research area look into existence from couple of decades. It has numerous applications in different technologies, for example: - Nano figuring, Bio sub-atomic calculations, Spacecraft, Quantum PCs, DNA registering, Field programmable Gate Array (FPGAs) in CMOS technology. The fundamental reason for planning BCD adder by utilizing complimentary gates is to diminish quantum cost and the quantity of waste outputs. The fundamental motivation behind the paper is to portray the correlation in Quantum cost, undesired output in the middle of BCD Adder using complimentary logic gates.Â Â Â